Enhancement animal manure compost value by using effective microbial - Tee, Tuan Poy; Majuntin, J.; Ooi, Peck Toung; Liang, Juan Boo (Tribun EU, 2011)
Intensive pig farming uses to generate excessive animal manure under a confine space. This excessive animal manure can be managed by composting process to utilize it as an organic fertilizer. Duration of composting process can be shortening by using effective microbial, Effective microbial (EM) are defined as group of beneficial microorganisms that are claimed to enhance microbial activity in compost and soil, which may increase their nutrients value. In view of that a study on evaluation the effective of EM composting process was conducted on pig manure from an intensive pig farm. Two compost piles were set up based on 2 different treatments; (I) Compost without EM or as a control, (II) Compost with EM. The ingredients (manure, sawdust, charcoal, limestone and EM) were well mixed under shed on concrete flooring. Each treatment was turned over weekly to allow aeration. The samples of compost piles were collected every 5 subsequent day for their nutrients analysis, and in situ parameters were measured daily. In terms of EM efficiency, it was found that temperature and pH of compost treated with EM were higher than the control result. The result showed that compost with EM had better nutrient values than compost without EM in terms of nutrient contents. Total nitrogen content was increased about 4% and 7% gain for TI and TII, respectively. However, a decrease of P and K content about 16% and 8%, respectively found in TI. A decrease result of P about 2.5% and no change of K content in TII. The C/N ratio was decreased about 13.5% and 23% for TI and TII, respectively.